Educational Values In The 15th Hadith Of The Book Of Al-Arba'in An-Nawawiyah By Imam An-Nawawi - Yayah Fauziyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
. Moral education is education that is very important in order to gain progress in living perfection both in relation to God and to fellow human beings. Because in today's era humans are more concerned with brain intelligence without being based on strong morals. Not even a few people who only think about their own benefits without thinking about the feelings of others. This research was made to find out the Values of Moral Education in the 15th Hadith of Al-Arbain An-Nawawi by Imam Nawawi. The type of this research is library research. This research was conducted by collecting data from various sources such as books, books, interpretations, the Koran which were raised and used as material in the research. In this step the author copies from the data books and books written by Imam an-Nawawi or Syarah about the book al-Arbain an-Nawawi and notes from educational experts contained in books, articles, journals, and so on. The conclusion of this study is that the educational values contained in the 15th hadith in the book of ak-Arbain an-Nawawi explain that whoever believes in Allah and the Last Day, we must always say good, if we cannot say good, then it is better silent, always glorifying neighbors, and always glorifying guests.